2008
DOI: 10.1002/bio.1015
|View full text |Cite
|
Sign up to set email alerts
|

Studies of visible oscillating chemiluminescence in luminol–H2O2–KSCN–CuSO4 system using (2‐hydroxyethyl) trimethylammonium hydroxide

Abstract: Visible oscillating chemiluminescence (CL) of luminol-H2O2-KSCN-CuSO4 was studied using the organic base (2-hydroxyethyl)trimethylammonium hydroxide. The effect of concentrations of luminol, H2O2, KSCN, CuSO4 and the base were investigated in a batch reactor. This report shows how the concentration of components involved in the oscillating CL system influenced the oscillation period, light amplitude and total time of light emission. The oscillating CL with different bases was also investigated. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…3. The overall chemiluminescence intensity becomes weaker as the initial concentration of Cu 2+ increases, as reported by Samadi-Maybodi et al 6 and Sorouraddin et al 9 Figure 4 shows the effect of the initial reagent concentration on the chemiluminescence intensities and ORP, where the initial concentration of H 2 O 2 was varied from 0.038 to 0.50 M, keeping the concentration of the other reagents constant. At the lowest concentration of H 2 O 2 , no oscillation was detected.…”
Section: The Interval Between the Adjacent Pulsed Emissionsupporting
confidence: 56%
See 1 more Smart Citation
“…3. The overall chemiluminescence intensity becomes weaker as the initial concentration of Cu 2+ increases, as reported by Samadi-Maybodi et al 6 and Sorouraddin et al 9 Figure 4 shows the effect of the initial reagent concentration on the chemiluminescence intensities and ORP, where the initial concentration of H 2 O 2 was varied from 0.038 to 0.50 M, keeping the concentration of the other reagents constant. At the lowest concentration of H 2 O 2 , no oscillation was detected.…”
Section: The Interval Between the Adjacent Pulsed Emissionsupporting
confidence: 56%
“…Samadi-Maybodi et al 5 investigated this phenomenon and proposed a possible reaction mechanism based on the results obtained by the addi-tion of (2-hydroxyethyl)trimethylammonium hydroxide, tetramethyl ammonium hydroxide, ethylenediamine, and methionine. [6][7][8] Sorouraddin et al 9,10 examined chemiluminescence during the addition of thiosemicarbazide, triethylenetrtramine, and D-penicillamine. They found that an oscillating chemiluminescence reaction occurred even with 1,10-phenanthroline instead of luminol 11 and afterward summarized their findings.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known luminol oscillating CL system in which a reacting chemiluminescing (luminol) is allowed to interact with a known Epstein-Orban chemical oscillator reaction, H 2 O 2 -KSCN-CuSO 4 -NaOH, was reported by Amrehn et al in 1988 (5). Samadi-Maybodi et al also studied visible oscillating CL of luminol-H 2 O 2 -KSCNCuSO 4 using an organic base (7,8). Recently, a thiosemicarbazide oscillating CL system was reported by our research group (9,10), which was CL produced by addition of thiosemicarbazide (TSC), a chemiluminescent reagent (11,12), to the oscillating system H 2 O 2 -KSCN-CuSO 4 -NaOH (9,10).…”
Section: +mentioning
confidence: 95%
“…Chemiluminescence (CL) analysis is a simple, rapid, and sensitive analytical method (1–3). Some catalysts, such as metal ions, metal complex and enzymes, can be used to effectively catalyze the CL reaction (4–7). Recent research has shown that gold nanoparticles (NPs), one of the most widely used noble metal nanomaterials, could also participate in CL reactions as a catalyst (8–10).…”
Section: Introductionmentioning
confidence: 99%